Evaluation of factors Affecting Intraoperative And Postoperative Hemorrhage in Percutaneous Nephrolithotomy (East West Medical College Journal, 2026)
Objective: There are many factors that are thought to affect hemorrhage associated with Percutaneous Nephrolithotomy (PCNL). This study was designed to evaluate factors affecting intraoperative and postoperative hemorrhage associated with PCNL. Patients and Methods: This prospective observational study was carried out in the Department of Urology, National Institute of Kidney Diseases and Urology, Dhaka, from December 2020 to December 2021. Total 87 patients with renal stone were selected by purposive sampling. Blood loss was estimated by the postoperative drop in hemoglobin and hematocrit after 48 hours of operation. Association of five patient-related factors (Diabetes mellitus, Hypertension, renal parenchymal thickness, stone burden and previous ipsilateral intervention) and five procedure-related factors (size of the tract, number of tracts, operation time, calyx of puncture and intraoperative complications) with hemorrhage was assessed using multiple linear regression analysis. Analysis of means was done by Independent sample t-test and one-way ANOVA test. Results: The mean ± SD for hemoglobin and hematocrit drop was 1.95 ± 0.87 gm/dl and 6.18 ± 2.36 % respectively. Multiple linear regression analysis showed that Diabetes mellitus (P=0.001), Hypertension (P=0.01), Renal parenchymal thickness (P=0.03), Stone burden (P=0.02), Previous ipsilateral intervention   (P=0.001), Size of the tract (P=0.0001), Number of tracts (P=0.0001), Operation time (P=0.004) and Intraoperative complications (P=0.0001) were significant predictors of hemorrhage.  Overall blood transfusion rate for all patients was 17.24 %. Diabetes mellitus, Number of tracts, Operation time and Intraoperative complications were significant predictor of perioperative blood transfusion requirement. One factor- Calyx of puncture, was found to have no effect on hemorrhage. Conclusion: Diabetes mellitus, Hypertension, increased stone burden, larger tract size, multiple tracts, prolonged operation time and occurrence of intraoperative complications are associated with increased hemorrhage during and after PCNL. Atrophic renal parenchyma and previous ipsilateral intervention are associated with reduced hemorrhage.EWMCJ Vol. 14, No. 2, July 2026: 116-123